2022
DOI: 10.3390/app12105035
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Hippocampus Identifies Network Alterations in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by rapid brain cell degeneration affecting different areas of the brain. Hippocampus is one of the earliest involved brain regions in the disease. Modern technologies based on high-throughput data have identified transcriptional profiling of several neurological diseases, including AD, for a better comprehension of genetic mechanisms of the disease. In this study, we investigated differentially expressed genes (DEGs) from six Gene Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…These results are supported by another study that found decreased CACNG2 gene expression levels in the prefrontal cortex of schizophrenia patients [66]. In AD, consistent with our observed hypomethylation at the CACNG2 gene body [30], another study also noted decreased CACNG2 gene expression in the hippocampus of AD patients [67].…”
Section: Utility and Discussionsupporting
confidence: 91%
“…These results are supported by another study that found decreased CACNG2 gene expression levels in the prefrontal cortex of schizophrenia patients [66]. In AD, consistent with our observed hypomethylation at the CACNG2 gene body [30], another study also noted decreased CACNG2 gene expression in the hippocampus of AD patients [67].…”
Section: Utility and Discussionsupporting
confidence: 91%
“…Five publicly available datasets of gene expression profiles of Alzheimer patients (GSE1297, GSE5281, GSE36980, GSE29378, and GSE48350) were downloaded from the Gene Expression Omnibus (GEO). These datasets contain the gene expression profiles of hippocampus of Alzheimer patients as this brain area is involved in the early stages of disease (Quarato et al 2022 ). We considered hippocampus because we suppose that this part of brain plays a fundamental role in different traits associated with AD.…”
Section: Methodsmentioning
confidence: 99%